Ecological Impact Assessment. - Treweek, Jo (John Wiley & Sons, 2009)
The world's ecosystems are increasingly threatened by human development. Ecological impact assessment (EcIA) is used to predict and evaluate the impacts of development on ecosystems and their components, thereby providing the information needed to ensure that ecological issues are given full and proper consideration in development planning. Environmental impact assessment (EIA) has emerged as a key to sustainable development by integrating social, economic and environmental issues in many countries. EcIA has a major part to play as a component of EIA but also has other potential applications in.